1995
DOI: 10.1128/jb.177.12.3455-3464.1995
|View full text |Cite
|
Sign up to set email alerts
|

Role for the histone-like protein H-NS in growth phase-dependent and osmotic regulation of sigma S and many sigma S-dependent genes in Escherichia coli

Abstract: TheS subunit of RNA polymerase (encoded by the rpoS gene) is the master regulator in a complex regulatory network that controls stationary-phase induction and osmotic regulation of many genes in Escherichia coli. Here we demonstrate that the histone-like protein H-NS is also a component of this network, in which it functions as a global inhibitor of gene expression during the exponential phase of growth. On two-dimensional gels, at least 22 S -controlled proteins show increased expression in an hns mutant. H-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
189
0
3

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(209 citation statements)
references
References 50 publications
14
189
0
3
Order By: Relevance
“…evolved second-site suppressor mutants. These strains yielded highly variable ␤-galactosidase activities obviously dependent on the specific nature of the second-site suppressor strains that took over the cultures when cells were grown in liquid medium [this effect was much more pronounced than in mutants deficient in hns alone, in which at least fresh transductants can be reliably assayed (Barth et al, 1995)]. …”
Section: Overexpression Of Leuo Results In Reduced Rpos Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…evolved second-site suppressor mutants. These strains yielded highly variable ␤-galactosidase activities obviously dependent on the specific nature of the second-site suppressor strains that took over the cultures when cells were grown in liquid medium [this effect was much more pronounced than in mutants deficient in hns alone, in which at least fresh transductants can be reliably assayed (Barth et al, 1995)]. …”
Section: Overexpression Of Leuo Results In Reduced Rpos Expressionmentioning
confidence: 99%
“…This factor is the LysR-like regulator, LeuO, which is shown to reduce rpoS translation mainly at low temperature by inhibiting the expression of DsrA-RNA. In addition, we found that H-NS is a potent repressor or even silencer of leuO, indicating that H-NS, while having a strong and general inhibitory role in the control of rpoS translation (Barth et al, 1995;Yamashino et al, 1995), also positively affects the level of DsrA-RNA, i.e. an activator of rpoS translation, by maintaining low levels of the dsrA repressor LeuO.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The amount of S increases in high-osmolarity medium, upon entry into stationary phase, at the onset of carbon or phosphate starvation and at low temperature (Lange and Hengge-Aronis, 1994;Gentry et al, 1993, Sledjeski et al, 1996. In hns mutants the concentration of S is increased more than 10-fold relative to a wild-type strain grown exponentially at low osmolarity (Yamashino et al, 1995;Barth et al, 1995). The increased expression in hns mutants of a number of genes transcribed in a S -dependent manner might therefore be affected indirectly by the increased S concentration (Table 1).…”
Section: Modulation Of Rpos Expressionmentioning
confidence: 99%
“…In general they grow more slowly than wild-type strains (Barth et al, 1995;Yamashino et al, 1995), they show increased osmosensitivity (Barth et al, 1995) and a prominent growth lag upon a shift to low temperature . A key to how hns mutants can display such pleitropic phenotypes was obtained when it was demonstrated that H-NS affects transcription of many unrelated genes and that the level of synthesis of more than 30 proteins is changed in hns mutants (Barth et al, 1995;Bertin et al, 1990;Yamada et al, 1991). Furthermore, H-NS is involved, directly or indirectly, in many other biological processes (see Ussery et al (1994) for a review).…”
Section: Introductionmentioning
confidence: 96%